Community-level chlamydial serology for assessing trachoma elimination in trachoma-endemic Niger. - Jessica S Kim; Catherine E Oldenburg; Gretchen Cooley; Abdou Amza; Boubacar Kadri; Baido Nassirou; Sun Yu Cotter; Nicole E Stoller; Sheila K West; Robin L Bailey; Jeremy D Keenan; Bruce D Gaynor; et al. (PLoS Neglected Tropical Diseases, 2019)
BACKGROUND:Program decision-making for trachoma elimination currently relies on conjunctival clinical signs. Antibody tests may provide additional information on the epidemiology of trachoma, particularly in regions where it is disappearing or elimination targets have been met. METHODS:A cluster-randomized trial of mass azithromycin distribution strategies for trachoma elimination was conducted over three years in a mesoendemic region of Niger. Dried blood spots were collected from a random sample of children aged 1-5 years in each of 24 study communities at 36 months after initiation of the intervention. A multiplex bead assay was used to test for antibodies to two Chlamydia trachomatis antigens, Pgp3 and CT694. We compared seropositivity to either antigen to clinical signs of active trachoma (trachomatous inflammation-follicular [TF] and trachomatous inflammation-intense [TI]) at the individual and cluster level, and to ocular chlamydia prevalence at the community level. RESULTS:Of 988 children with antibody data, TF prevalence was 7.8% (95% CI 6.1 to 9.5) and TI prevalence was 1.6% (95% CI 0.9 to 2.6). The overall prevalence of antibody positivity to Pgp3 was 27.2% (95% CI 24.5 to 30), and to CT694 was 23.7% (95% CI 21 to 26.2). Ocular chlamydia infection prevalence was 5.2% (95% CI 2.8 to 7.6). Seropositivity to Pgp3 and/or CT694 was significantly associated with TF at the individual and community level and with ocular chlamydia infection and TI at the community level. Older children were more likely to be seropositive than younger children. CONCLUSION:Seropositivity to Pgp3 and CT694 correlates with clinical signs and ocular chlamydia infection in a mesoendemic region of Niger. TRIAL REGISTRATION:ClinicalTrials.gov NCT00792922.